2021
DOI: 10.3389/fcell.2021.739594
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of the Tumor Microenvironment in Skin Cutaneous Melanoma Reveals a Prognostic and Immunotherapeutically Relevant Gene Signature

Abstract: The tumorigenesis of skin cutaneous melanoma (SKCM) remains unclear. The tumor microenvironment (TME) is well known to play a vital role in the onset and progression of SKCM. However, the dynamic mechanisms of immune regulation are insufficient. We conducted a comprehensive analysis of immune cell infiltration in the TME. Based on the differentially expressed genes (DEGs) in clusters grouped by immune infiltration status, a set of hub genes related to the clinical prognosis of SKCM and tumor immune infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Zhou et al. ( 38 ) demonstrated that the low expression of KIR2DL4 is significantly associated with poor prognosis in SKCM. Moreover, KIR2DL4 as a receptor on HLA-G, has been thought as one of potential targets for immunotherapy to treat cancer ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al. ( 38 ) demonstrated that the low expression of KIR2DL4 is significantly associated with poor prognosis in SKCM. Moreover, KIR2DL4 as a receptor on HLA-G, has been thought as one of potential targets for immunotherapy to treat cancer ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some of them have already been verified to play an important part in SKCM. Zhou et al (38) demonstrated that the low expression of KIR2DL4 is significantly associated with poor prognosis in SKCM. Moreover, KIR2DL4 as a receptor on HLA-G, has been thought as one of potential targets for immunotherapy to treat cancer (39) in both breast and melanoma cell lines and eventually proved that NMI retards tumor growth (40).…”
Section: Discussionmentioning
confidence: 99%
“…KIRP has a better prognosis in the early stages than clear cell malignancies, but the situation changes drastically after the cancer has spread to distant sites ( Zhao and Eyzaguirre, 2019 ). Pyroptosis has been linked to the emergence and progression of cancers in a growing body of data ( Liu et al, 2021 ; Zhang et al, 2021 ; Zhou et al, 2021 ). Pyroptosis has been found to slow the development of tumors in multiple cancers ( Sharma et al, 2019 ; Chen et al, 2020 ; Fenini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CLEC18B [ 18 ], CLEC12A [ 19 ], and CLEC11A [ 20 ] are associated with the development of various cancers. In contrast, the number of CTLs members namely CLEC3B [ 21 ], CLEC4G / M [ 22 ], and CLEC4E [ 23 ] are decreased in cancer cells, which have the potential to be suppressor genes in different cancers.…”
Section: Introductionmentioning
confidence: 99%